Policy brief: Outta trust? (Post)-pandemic trust and democratic resilience in the Western Balkans - Prelec, T; Vasiljević, J; Džihić, V; Kmezić, M (Balkans in Europe Policy Advisory Group (BiEPAG), 2021)
In the Western Balkans, issues linking trust and democracy acquire particular importance and urgency in the wake of the Covid crisis. Based on a large-scale public opinion poll carried out in the six countries of the Western Balkans, this brief shows that the pandemic has exacerbated the region’s issues with trust in public institutions even further. The study finds that the reticence of publics to undergo vaccination is directly linked with mistrust in governments, corroborating earlier research by BiEPAG that warned about the wide diffusion of coronavirus-related conspiracy theories in the region and their relation with vaccine scepticism. The brief also points to the profiling of a trend termed ‘authoritarian production of trust’ in the largest country of the region, Serbia. Yet, it also identifies a ‘constituency of change’ with similar characteristics across the region: a picture that opens space to invest trust in new actors able to advance genuine progressive causes in South East Europe, beyond and instead of captured institutions and the respective party establishments.